Cheminformatics of Natural Products. Volume 1, - Ntie-Kang, Fidele (De Gruyter STEM ;, 2020)
Vol. 1 of Chemoinformatics of Natural Products presents an overview of natural products chemistry, discussing the chemical space of naturally occurring compounds, followed by an overview of computational methods.- Resumé vydavatel